Odpowiedź :
Odpowiedź:
[tex]\begin{cases}2x-5y=-3\\3x+2y=-8\ \ /:2\end{cases}\\\\\\\begin{cases}2x-5y=-3\\\frac{3}{2}x+y=-4\end{cases}\\\\\\\begin{cases}2x-5y=-3\\y=-4-\frac{3}{2}x\end{cases}\\\\\\2x-5(-4-\frac{3}{2}x)=-3\\\\2x+20+\frac{15}{2}x=-3\ \ /\cdot2\\\\4x+40+15x=-6\\\\19x=-6-40\\\\19x=-46\ \ /:19\\\\x=-\frac{46}{19}[/tex]
[tex]y=-4-\frac{3}{\not2_{1}}\cdot(-\frac{\not46^2^3}{19})=-4+\frac{69}{19}=-4+3\frac{12}{19}=-3\frac{19}{19}+3\frac{12}{19}=-\frac{7}{19}\\\\\\\begin{cases}x=-\frac{46}{19}\\y=-\frac{7}{19}\end{cases}[/tex]